Circulating Inhibitor against Factor X: A Rare Cause of Hemorrhagic Diathesis - P. Rossignon; F. Grandjean; A. Claessens; N. Weynants (Case Reports in Hematology)
Acquired coagulopathies resulting from factor X deficiency are rare and typically associated with amyloidosis or plasma cell dyscrasia. Factor X plays a pivotal role in the coagulation cascade, converting prothrombin into thrombin and facilitating the formation of fibrinogen and thrombus. While its occurrence following common infections is extremely rare, isolated cases have been documented. We present a rare case of bleeding diathesis in a patient with community-acquired pneumonia, where prolonged activated partial thromboplastin time (aPTT) and prothrombin time (PT) led to the diagnosis of an infectious-triggered acquired circulating inhibitor targeting factor X. Prompt treatment with methylprednisolone effectively controlled the inhibitor without recurrence. This case report provides insights into the diagnostic strategies, differential algorithm, and therapeutic approaches for managing this rare coagulopathy.